Cyclic Oligolactic Acid in Direct Polycondensation PLLA and Its Extraction with Organic Solvent. (25th November 2014) - Nomura, Keiichiro; Nakatsuchi, Yuta; Shinmura, Ryugo; Pivsa-Art, Sommai; Pivsa-Art, Weraporn; Aso, Yuji; Ohara, Hitomi
Abstract : The contents of poly(l -lactic acid) (PLLA) prepared by direct condensation polymerization without using a catalyst were studied. 1 H NMR and mass spectrometry analyses suggested that PLLA contained cyclic oligo(l -lactic acid) (c-OLLA) with 3–20 repeat units. Notably, only c-OLLA was extracted and isolated using hexane or cyclohexane at 4°C; thus the hydrophobicity, topology, and temperature dependence of the solubility of the obtained PLLA enabled the selective extraction of c-OLLA. The effect of cyclic compounds on direct polycondensation and the potential for c-OLLA to form molecular inclusion complexes were also discussed.